THE CONTRIBUTION OF SATELLITE MULTISPECTRAL IMAGES IN GEOMORPHOLOGY, FROM THE 70'S (LANDSAT SATELLITES) TO THE PRESENT DAY (IKONOS, QUICKBIRD SATELLITES). EXAMPLES FROM GREECE. - ΑΣΤΑΡΑΣ, Θ.; ΟΙΚΟΝΟΜΙΔΗΣ, Δ.; ΜΟΥΡΑΤΙΔΗΣ, Α. (Bulletin of the Geological Society of Greece, 2005)
This paper describes initially the availability of multispectral satellite images, from the launch of the first Earth Resources Satellites (Landsat series), with medium resolution capabilities (80m), to the launch of the contemporary satellites (QuickBird, 2001), with very high resolution capabilities (60cm). It reviews researches, concerning the visual and digital image analyses of the LANDSAT series, SPOT, 1RS, TERRA and QuickBird satellite images that have been carried out during the last 20 years in the Department of Physical and Environmental Geography, School of Geology, Aristotle University of Thessaloniki. These researches are of geomorphological-geological interest and involve applications in various areas of Greece. In particular, practical examples are provided, concerning the detection and delineation of landslides in Macedonia and Epirus Provinces, the detection and classification of geomorphological units (land systems) in Peloponnesos, Thrace, Macedonia and Santorini areas and the analysis of drainage network in Central Macedonia Province with emphasis in the delineation of severe erosional phenomena. Reason for this review paper, is the contemporary use of Digital Elevation Models (DEMs) with 10-30 m accuracy, from the Shuttle Radar Topography Mission (SRTM / 2000) and their contribution, along with the high resolution satellite images, (from TERRA, QuickBird, etc), in the 3-D visualization of the Earths' relief. In particular, the use of 3-D satellite images will assist geoscientists and especially geomorphologists, to study the Earths' relief and its' evolution, more quickly, with better accuracy and at lower cost, compared with aerial photographs and 2-D satellite images, which have been used during the last 20 years.